Mathematical modelling of a linkage-based robotic finger. (2012) - Azlan, Norsinnira Zainul; Yamaura, Hiroshi
This paper presents the mathematical dynamic model development of a linkage-based robotic finger with fingertip pinching and self-adaptive grasping functions during non-contact mode. The finger's structure is made of a seven-bar linkage mechanism with a slider in the middle phalanx to adjust its effective length in accomplishing these two tasks. This study extends the dynamic models of the closed loop mechanism and hybrid actuator to describe the dynamic behaviour of the finger due to its mechanical linkages. The model is later integrated with the actuator model to represent the whole robotic system. Simulation and experimental tests of the robotic finger under the Proportional Integral (PI) control algorithm have been conducted to evaluate the validity of the proposed model.